Amelioration of human lupus-like phenotypes in MRL/lpr mice by overexpression of interleukin 27 receptor α (WSX-1). Issue 10 (18th December 2007) - Sugiyama, N; Nakashima, H; Yoshimura, T; Sadanaga, A; Shimizu, S; Masutani, K; Igawa, T; Akahoshi, M; Miyake, K; Takeda, A; Yoshimura, A; Hamano, S; et al.
Abstract : Objective: In the present work, we investigate the role of interleukin (IL)27/IL27 receptor α (Rα) (WSX-1) in the development of autoimmune disorders in the MRL/ lpr mouse, which is considered as an experimental model of systemic lupus erythaematosus (SLE) in humans. Methods: We generated two strains of WSX-1 transgenic mice in the MRL/ lpr background with different expression levels of WSX-1, and investigated the effect of WSX-1 overexpression on survival, glomerulonephritis and immunological properties. Results: In comparison with wild type (WT) MRL/ lpr and transgenic (Tg) low (TgL) mice, Tg high (TgH) mice exhibited a prolonged lifespan and no apparent development of autoimmune nephritis. Production of anti-dsDNA antibody and total IgG and IgG2a were significantly lower in TgH mice than those of TgL and WT mice. The expressed amounts of interferon (IFN)γ and IL4 mRNA by CD4 + T cells from Tg mice decreased in a dose-dependent fashion. CD4 + splenic lymphocytes in TgH mice were more subject to the IL27-mediated suppression of cytokine production. In vitro stimulation of CD4 + T cells by IL27 resulted in over phosphorylation of STAT3 in TgH cells than in WT cells. Conclusion: WSX-1 overexpression in the MRL/ lpr background rendered the autoimmune prone mice protected from the development of autoimmune diseases. Our results suggest that IL27 signalling may be a therapeutic target against autoimmune diseases, including human SLE.